Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45673
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Unsteady Turbine Flow on the Performance of an Exhaust Diffuser

Abstract: For the design of highly efficient turbine exhaust diffusers, it is important to take into account the unsteady flow field induced by the last turbine stage. A 1/10 scale model of a gas turbine exhaust diffuser consisting of an annular followed by a conical diffuser is used to investigate the influence of the unsteady flow conditions on the performance of the diffuser. To reproduce the outflow of the last turbine stage, a NACA profiled rotor is placed at the inlet of the diffuser. Measurements with 3D hot-wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The findings were experimentally validated by Sieker and Seume (2008). Kuschel and Seume (2011) conducted additional experiments using a NACA profile instead of cylindrical spokes. A detailed analysis of these experimental results can be found in Kuschel et al (2015) and Drechsel et al (2015).…”
Section: Stabilisation Numbermentioning
confidence: 80%
“…The findings were experimentally validated by Sieker and Seume (2008). Kuschel and Seume (2011) conducted additional experiments using a NACA profile instead of cylindrical spokes. A detailed analysis of these experimental results can be found in Kuschel et al (2015) and Drechsel et al (2015).…”
Section: Stabilisation Numbermentioning
confidence: 80%
“…Turbine outflows are inherently unsteady and incorporate swirl and inhomogeneous flow conditions due to tip leakage flows and wakes. These conditions were also found to affect the diffuser flow considerably [3][4][5][6][7]. Sieker and Seume [5] showed that highly turbulent, unsteady inflow can stabilize the flow field even if the diffuser was predicted to separate according to the diffuser charts.…”
Section: Introductionmentioning
confidence: 99%
“…Sieker and Seume [5] showed that highly turbulent, unsteady inflow can stabilize the flow field even if the diffuser was predicted to separate according to the diffuser charts. Kuschel and Seume [7] showed the impact of unsteady coherent vortices at the blade tips using unsteady hot-wire probes. Furthermore, they came to the conclusion that the Reynolds stresses of the rotor outflow at the blade tip are anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…The Kluss study demonstrated through comparison with experiment that URANS CFD calculations simulating an upstream rotor, coupled with an anisotropic turbulence model are necessary to provide a reasonable prediction of turbine exhaust diffuser performance. Further efforts [79] on the same test rig confirmed the need for URANS calculations and anisotropic turbulence modelling, and revealed that turbine rotor tip clearance flows are a key feature in diffuser performance. Additional momentum close to the shroud surface, afforded by the tip gap, supports the boundary layer against the adverse pressure gradient within the diffuser and enables efficient operation of a more compact diffuser.…”
Section: Introductionmentioning
confidence: 80%
“…Contrasting the inlet delivery system, interactions between components are significant in determining performance and optimum geometry of the diffuser. Recent studies [78,79,80,81,82] indicate that rotor -diffuser interactions are significant, and that fully coupled, URANS stage simulations are necessary to resolve diffuser component performance. The use of such a modelling framework leads to more compact, higher performing diffuser geometries than would otherwise be designed had the interactions not been accounted for.…”
Section: Modelling Segregationmentioning
confidence: 99%